2008
DOI: 10.1016/j.mrgentox.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DNA repair capacity in whole blood of patients with head and neck cancer and healthy donors by comet assay

Abstract: Comet assay has been used to estimate cancer risk by quantification of DNA damage and repair in response to mutagen challenge. Our goal was to adopt best practices for the alkaline comet assay to measure DNA repair capacity of white blood cells in whole blood of patients with squamous cell carcinoma of the head and neck (HNSCC). The results show that initial damage by 10 Gy of gamma radiation expressed as percent DNA in comet tail was higher in stimulated lymphocytes (61.1±11.8) compared to whole blood (43.0±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The study of Schmezer et al did not detect any significant difference between the levels of baseline DNA damage in lymphocytes of lung cancer patients and healthy individuals but found an increased sensitivity of lymphocytes to bleomycin and decreased DNA repair capacity in cancer patients [20]. The deficient DNA repair in lymphocytes of lung, head and neck cancer patients also has been shown by other researchers [4, 5, 8, 9]. It should be mentioned that the concentration of bleomycin (20 μg/ml) recommended by Schmezer et al, which we also used in our study, caused DNA damage at saturation level of the assay.…”
Section: Discussionmentioning
confidence: 82%
“…The study of Schmezer et al did not detect any significant difference between the levels of baseline DNA damage in lymphocytes of lung cancer patients and healthy individuals but found an increased sensitivity of lymphocytes to bleomycin and decreased DNA repair capacity in cancer patients [20]. The deficient DNA repair in lymphocytes of lung, head and neck cancer patients also has been shown by other researchers [4, 5, 8, 9]. It should be mentioned that the concentration of bleomycin (20 μg/ml) recommended by Schmezer et al, which we also used in our study, caused DNA damage at saturation level of the assay.…”
Section: Discussionmentioning
confidence: 82%
“…Results of Saha et al (2008) also showed a slower DNA repair efficiency in HNSCC patients in comparison to healthy donors, measured by alkaline comet assay. The repair was slightly higher in controls compared with HNSCC patients who were matched based on age and smoking status.…”
Section: Discussionmentioning
confidence: 91%
“…g-radiation indicated higher level of endogenous DNA damage and decreased efficacy of DNA repair in comparison to lymphocytes taken from healthy donors. After 15 min of repair incubation, a higher level of DNA damage and slower DNA recovery than in lymphocytes taken from control subjects was observed (Saha et al, 2008). Palyvoda et al (2002) also showed decreased repair in HNSCC patients.…”
mentioning
confidence: 94%